The toxicity and efficacy of two formulations of acephate on two populations of Plutella xylostella L. (lepidoptera: plutellidae) - Mohamad, Rosli; Baharom, Roslee (Malaysian Society of Applied Biology, 1984)
Laboratory toxicity and field effectiveness of two formulations of acephate, technical (97%) and Orthene 75SP, were evaluated on two populations of Plutella xylostella. In the laboratory, larvae were exposed to treated leaves of Indian mustard (Brassica juncea) for 48 h. At the lowest (0.05% a.L) and the highest (0.2% a.L) concentrations tested, both formulations caused Inortalities of > 55% and > 80%, respectively on the two populations. In the field, the two formulations were equally effective in lowering the Leaf Damage Index on cabbage (Brassica oleraceae var. capitata). At all concentrations tested, the number of marketable heads obtained was significantly greater (p <0.05) than that of control. In terms of the Leaf Damage Index and the percentage marketable heads, increasing concentrations of either formulations reduced the former and increased the latter for both populations.